Strategi Adaptasi Dan Mitigasi Pembakaran Sampah Terbuka di Kenali Asam Bawah, Kota Jambi - Naoval Arjuna Pramudya; Lailal Gusri (JURNAL ILMIAH NUSANTARA, 2025)
Open waste burning remains a common practice in Kenali Asam Bawah, Jambi City, with significant impacts on environmental quality and public health. This study aims to identify the practice, analyze its impacts, and formulate contextual adaptation and mitigation strategies. This qualitative descriptive research employed a case study approach through field observations, interviews with residents and community leaders, and document analysis. The findings reveal that waste burning is driven by inadequate waste collection services and limited awareness of its consequences. The waste includes organic and inorganic materials, producing harmful emissions such as PM2.5, dioxins, and heavy metals. These emissions contribute to respiratory problems, air and soil pollution, and potential disruption of local ecosystems. Recommended strategies include environmental education, strengthening of local institutions, development of waste management infrastructure, innovation in household waste processing, and reinforcement of anti-burning regulations. The study is expected to contribute to local emission reduction efforts and support sustainable waste management practices.